2021
DOI: 10.1038/s41598-021-99395-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the carbon capture potential of a reforestation project

Abstract: The number of reforestation projects worldwide is increasing. In many cases funding is obtained through the claimed carbon capture of the trees, presented as immediate and durable, whereas reforested plots need time and maintenance to realise their carbon capture potential. Further, claims usually overlook the environmental costs of natural or anthropogenic disturbances during the forest’s lifetime, and greenhouse gas (GHG) emissions associated with the reforestation are not allowed for. This study uses life c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 50 publications
3
20
0
1
Order By: Relevance
“…We also identified lower relative abundance of microbes associated with ammonia oxidation in soils from locations with high human populations. AOA and AOB have been found to be affected by increased heavy metal pollution, including Cd, Cu, and Pb, which were found in this study to be significantly positively correlated with the human population …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We also identified lower relative abundance of microbes associated with ammonia oxidation in soils from locations with high human populations. AOA and AOB have been found to be affected by increased heavy metal pollution, including Cd, Cu, and Pb, which were found in this study to be significantly positively correlated with the human population …”
Section: Discussionsupporting
confidence: 57%
“…In this data set, we found that grass-dominated soils tended to be a “middle ground” in terms of the measured variables, suggesting grassland to be a buffered soil type, capable of withstanding pressures from chemical and physical disturbances. The prevailing mindset is that regeneration of woodlands is one of the most effective ways to combat increasing greenhouse gas (GHG) emissions; however, more recently, it has been suggested that many reforestation projects do not take into account the GHGs produced by the creation of woodlands and from the woodlands once they are established . This study and those such as Dass et al agree that, if conversion of land to woodland comes at the expense of losing grassland habitats, this is also a loss of important GHG sinks …”
Section: Discussionmentioning
confidence: 77%
“…Reforestation and forest restoration are considered key strategies for tackling climate change by enhancing CO 2 sequestration ( Lefebvre et al, 2021 ; Domke et al, 2020 ; Nave et al, 2019 ). Under the European Green Deal and the European biodiversity strategy for 2030, the European Union has committed to plant at least three billion additional trees by 2030 ( European Commission, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how these plants respond to eCO 2 may guide scientists and decision-makers in deriving climatesmart mitigation strategies (Hu et al 2018). Amongst other disciplines, forestry plays a pivotal role in climate change mitigation by increasing C sinks through afforestation/reforestation (Lefebvre et al 2021). For this reason, woody plant responses to eCO 2 require a special scientific assessment (Wang and Wang 2021a).…”
Section: Introductionmentioning
confidence: 99%